Low-Cost Country Sourcing Trends and Implications - Lockström, Martin; SpringerLink (Online service) (Wiesbaden : Deutscher Universitätsverlag : Imprint: Deutscher Universitätsverlag, 2007)
Globalization has induced immense cost pressure in most industries. In combination with the economic downturn after the turn of the century, companies are increasingly looking for new ways of reducing costs and increasing shareholder value. From this perspective, low-cost country sourcing has proved to be an effective means to realize cost-saving targets. Although many external key success factors have been identified, relatively little is known about intra-firm factors that can influence the outcome of low-cost country sourcing initiatives. On the basis of a pan-European survey conducted among senior purchasing managers of 200 large-sized multinationals, Martin Lockström identifies internal key success factors of companies sourcing in low-cost countries. It is shown that internal factors play a significant role for the shopping achievement of an enterprise and that the respected magnitude of shopping activities in low-cost countries will rise within the next five years.
Frame of Reference on Low-Cost Country Sourcing: A Literature Review -- Research Methodology -- Low-Cost Country Sourcing Trends: A Descriptive Study -- Implications of Low-Cost Country Sourcing: An Explanatory Study -- Summary and Conclusions.
Keywords: Industrial procurement; Management; Procurement; Management